2016
DOI: 10.20344/amp.6905
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Death in an Acute Psychiatric Inpatient Unit of a Portuguese General Hospital

Abstract: Mortality studies are important for determining quality of health care and to create recommendations for preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
7
0
1
Order By: Relevance
“…PE is a relatively common and largely preventable cause of death for psychiatric patients [7]. Evidence shows a significantly increased risk of venous thromboembolism and PE in antipsychotic users compared to non-users [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PE is a relatively common and largely preventable cause of death for psychiatric patients [7]. Evidence shows a significantly increased risk of venous thromboembolism and PE in antipsychotic users compared to non-users [8].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows a significantly increased risk of venous thromboembolism and PE in antipsychotic users compared to non-users [8]. A chart review study in Japan between May 1, 2009, and April 30, 2017, showed that catatonia was associated with an increased incidence of VTE [6][7][8]. According to the study conducted by Barbosa et al, among the causes of death in "unit of a Portuguese general hospital among the acute psychiatric inpatients," the main causes were circulatory system disorders (66.66%), mainly PE (28.57%) and stroke (14.29%) [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caro editor, Em 2016 foi publicado nesta revista o artigo "Causas de Morte numa Unidade de Internamento de Agudos de Psiquiatria de um Hospital Geral Português", que concluiu que o tromboembolismo pulmonar foi a principal causa de morte no internamento psiquiátrico do Hospital Fernando Fonseca no período analisado de 1998 a 2013. 1 Este estudo alertou-nos para a problemática do tromboembolismo venoso (TEV) nos doentes psiquiátricos internados, sobre a qual gostaríamos de tecer algumas considerações.…”
Section: Fontes De Financiamentounclassified